Unexpected intraoperative finding of a hyalinizing cholecystitis in a patient with gallbladder calculi - Gjinoska, Klaudia; Nikolovski, Andrej; Stoicovski, Emil; Mitrev, Zan (Oxford University Press (OUP), 2024)
Hyalinizing cholecystitis is a rare subtype of chronic cholecystitis in which the gallbladder tissue is replaced with hyaline sclerosis, more or less, and has a characteristic intraoperative appearance. Preoperative diagnosis is hard to establish. The entity is strongly associated with gallbladder carcinoma. Therefore, the pathologist should perform a thorough microscopic analysis. We present a case of an unusual intraoperative finding in a male patient with chronic cholecystitis which was proved to be a hyalinizing cholecystitis.